Symptoms indicative of early knee osteoarthritis after ACL reconstruction: descriptive analysis of the SHIELD cohort - Anna Cronström; May Arna Risberg; Martin Englund; Dorthe B. Strauss; Paul Neuman; Carl Johan Tiderius; Eva Ageberg (Osteoarthritis and Cartilage Open)
Objective: To describe the SHIELD cohort in terms of symptoms indicative of early knee osteoarthritis (OA) and to investigate associations between patient characteristics (demographics, activity/injury-related) and these symptoms at 1 (cross-sectional) and 3 years (longitudinal) post anterior cruciate ligament reconstruction (ACLR). Method: 106 participants (50 ​% women, mean [SD] age 25 [5] years) were included. Symptoms indicative of early knee OA were evaluated by the Knee injury and Osteoarthritis Outcome Score (KOOS) subscale pain, KOOS subscale pain ≤72 (KOOSpain ≤72), and ≤85 on two out of four KOOS subscales (pain, symptoms, activity of daily living, quality of life) (modified Luyten). Results: Mean (SD) KOOS pain scores were 83.2 (15.7) and 87.3 (12.7) at 1 and 3 years, respectively. At 1 year and 3 years post ACLR, 18/101 (18 ​%) and 14/86 (16 ​%) participants met the KOOSpain ≤72 criterion, whereas 83/101 (82 ​%) and 67/86 (78 ​%) met the modified Luyten criterion. 7/15 (47 ​%) (KOOSpain ≤72) and 59/70 (84 ​%) (modified Luyten) classified as having knee OA symptoms 1 year post ACLR were still classified as having OA symptoms after 3 years. Lower activity level at 1 year was the sole variable consistently associated with all three outcomes 3 years post ACLR. Conclusion: The proportion of participants fulfilling existing classification criteria for symptoms indicative of early OA after ACLR is highly dependent on the criteria applied and different criteria seem to capture varying aspects of early OA symptoms. Future studies will reveal if these symptoms will persist long-term or just reflect more transient issues.